Recruitment, Engagement, and Retention of Fathers in Nutrition Education and Obesity Research - Vollmer, Rachel L.; Adamsons, Kari; Mobley, Amy R. (Journal of nutrition education and behavior, 2019)
This article provides a perspective about recruiting, engaging, and retaining fathers in research and programming related to nutrition education and childhood obesity prevention. Recent research emphasizes the importance of fathers in childhood obesity prevention, and although father-friendly approaches can emulate other underserved populations, some researchers have acknowledged that differences may exist. Family sciences– related and nutritional sciences–related literature is summarized to provide guidance for nutrition and obesity scholars. Best practices may vary by the type of study and father characteristics; and the venues, content, structure, timing, and approach of research and interventions may need to be tailored for fathers.